EXPLORING THE IMPACT OF AGE AND MOTIVATION ON SELF-DETERMINATION: INSIGHTS FROM INFORMAL SECTOR MOTHERS - Heriberta, Heriberta; Zulfanetti, Zulfanetti; Setiawati, Rike (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2024)
This groundbreaking research explores the intricate interplay between age factors, motivation to work, and the self-determination of mothers engaged in the informal employment sector, a demographic often overlooked in scholarly investigations. Employing a mixed-method approach characterized by a sequential exploratory design, this study pioneers a comprehensive examination of the multifaceted dynamics shaping maternal self-determination. Leveraging purposive sampling, data collection unfolds through a meticulously orchestrated blend of orally administered questionnaires and in-depth interviews, ensuring a holistic understanding of the subject matter. Analytically, the research employs a dual-pronged strategy encompassing descriptive and inferential statistical analyses, complemented by Miles & Huberman’s framework for interview analysis. The study unveils a significant nexus between age, motivation, and maternal self-determination through rigorous statistical scrutiny, filling a conspicuous void in extant literature. This research’s novelty lies in its explicit focus on delineating the intricate correlations and synergies between age and motivation factors vis-a-vis self-determination, particularly within the context of working mothers operating within informal economies, an underexplored realm in academic discourse. The implications of this study reverberate far beyond academia, offering tangible insights that can inform the development of targeted support programs tailored to empower and uplift mothers navigating the informal employment sector. Ultimately, this research represents a pioneering stride towards fostering a more inclusive and equitable ecosystem for working mothers, underpinned by a nuanced understanding of their unique challenges and aspirations.